Targeted gene sequencing and bioinformatics analysis of a patient with gallbladder adenosquamous carcinoma: a case report - Gu, Yangjun; Chen, Zhitao; Fang, Qingqing; Li, Qiyong (Frontiers in Oncology, 2026)
IntroductionGallbladder adenosquamous carcinoma (GBASC) is an uncommon, highly aggressive neoplasm characterized by the coexistence of both glandular and squamous cells. Representing fewer than 5% of gallbladder malignancies, GBASC demonstrates a more aggressive behavior and has poorer prognosis, posing considerable challenges for early diagnosis and effective management.Case presentationWe present a case of GBASC in a 52-year-old woman who achieved long-term tumor-free survival by surgery, as well as targeted and immunotherapy after the operation. Targeted gene sequencing and bioinformatics analysis tools, including STRING, GeneMANIA, Metascape, TRRUST, Sangerbox, and cBioPortal, were used to analyze the biological functions and features of the mutated genes in GBASC. A total of 16 mutations (NF2, EGFR, EPHA2, CDK6, LATS2, NBN, CUL3, FRAS1, ATM, KMT2A, EXT1, SMARCA1, RECQL4, KMT2D, POLQ, and CTNND2) were identified, and the tumor mutation burden was determined to be 5.73 mut/Mb via targeted gene sequencing. The protein–protein interaction network highlighted robust connections among the 16 mutated genes. Functional enrichment via Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses pinpointed tumor-associated signaling cascades. Moreover, based on bioinformatics analysis, the key points at the treatment duration of this patient were discussed.ConclusionsComparative analyses with other gallbladder carcinoma subtypes revealed GBASC to have distinct clinical phenotypes, molecular alterations, functional characteristics, and enriched signaling pathways. Moreover, there is an urgent need for standardized treatment protocols.